Genetic markers cannot determine Jewish descent - Falk, Raphael (Frontiers in Genetics, 2015)
Humans differentiate, classify, and discriminate: social interaction is a basic property of human Darwinian evolution. Presumably inherent differential physical as well as behavioral properties have always been criteria for identifying friend or foe. Yet, biological determinism is a relatively modern term, and scientific racism is, oddly enough, largely a consequence or a product of the Age of Enlightenment and the establishment of the notion of human equality. In recent decades ever-increasing efforts and ingenuity were invested in identifying Biblical Israelite genotypic common denominators by analysing an assortment of phenotypes, like facial patterns, blood types, diseases, DNA-sequences, and more. It becomes overwhelmingly clear that although Jews maintained detectable vertical genetic continuity along generations of socio-religious-cultural relationship, also intensive horizontal genetic relations were maintained both between Jewish communities and with the gentile surrounding. Thus, in spite of considerable consanguinity, there is no Jewish genotype to identify.